2012
DOI: 10.1136/oemed-2011-100615
|View full text |Cite
|
Sign up to set email alerts
|

Physically demanding work, fetal growth and the risk of adverse birth outcomes. The Generation R Study

Abstract: Long periods of standing and long working hours per week during pregnancy seem to negatively influence intrauterine growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 42 publications
5
58
1
3
Order By: Relevance
“…They found that no convincing associations were observed between shift work and birth weight, however, fixed night work could be increased abortion and still birth (21). Henriksen TB et al and Snijder CA et al found no evidence that work, per-se, had any detrimental or beneficial effects on the risk of having a small for gestational age and risk of low birth weight was small (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…They found that no convincing associations were observed between shift work and birth weight, however, fixed night work could be increased abortion and still birth (21). Henriksen TB et al and Snijder CA et al found no evidence that work, per-se, had any detrimental or beneficial effects on the risk of having a small for gestational age and risk of low birth weight was small (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…The risk of adverse birth outcomes such as foetal death, preterm labor and low birth weight have been investigated in a number of studies in relation to physical and psychosocial work exposures, and the results of these studies have been conflicting (27)(28)(29)(30)(31). In general, if present, elevated risks for adverse birth outcomes are small, and currently there is no evidence to impose limits of physical exposures such as lifting, walking, or standing or even to discourage the exposures among healthy pregnant women.…”
Section: Hansen Et Almentioning
confidence: 99%
“…zaobserwowali związek między czasem pracy i dłu-gotrwale utrzymywaną pozycją stojącą a wewnątrz-macicznym wzrostem płodu [21]. U kobiet pracują-cych 25-39 godz.…”
Section: Wymiar Czasu Pracyunclassified
“…U kobiet pracujących powyżej 40 godz. w tygodniu odnotowano dodatkowo obniżenie masy urodzeniowej dziecka średnio o 148-198 g [21].…”
Section: Wymiar Czasu Pracyunclassified